Mental health functioning among men who use the Internet specifically to find partners for unprotected sex - Hugh Klein (Mental Illness)
Previous studies have shown a link between mental health functioning and involvement in HIV risk practices. The present research examines how well one specific group of men who have sex with other men (MSM) fare in terms of their mental health functioning, and then focuses on how mental health functioning relates to HIV risk practices in this population. The study was based on a national random sample of 332 MSM who use the Internet to seek men with whom they can engage in unprotected sex. Data collection was conducted via telephone interviews between January 2008 and May 2009. Depression is more common among men in this population than in the adult male population-at-large. All other measures of mental health functioning that were examined (self-esteem, impulsivity, current life satisfaction, optimism about the future) indicated low rates of mental health problem. Contrary to expectations, in nearly all instances, mental health functioning was not related to HIV risk practices. More work needs to be done to understand the causes of depression among these men, and to assess how, if at all, depression relates to risk practices in this population. These findings suggest that factors other than mental health problems must be considered if one wishes to understand HIV risk taking in this population.